How strong is the relationship between scabies and acute rheumatic fever? An analysis of neighbourhood factors. (27th November 2019) - Thornley, Simon; King, Ron; Marshall, Roger; Oakley, Amanda; Sundborn, Gerhard; Harrower, Jay; Reynolds, Edwin; Arbuckle, Mark; Johnson, Richard J.
Abstract : Aim: Recent studies have linked scabies with acute rheumatic fever (ARF). We explored the relationship, by neighbourhood, between permethrin dispensing as an indicator of scabies prevalence and ARF cases over the same period. Methods: Incident cases of ARF notified to public health between September 2015 and June 2018 and the annual incidence of prescribing by neighbourhood over the same period were analysed. Evidence of an association between permethrin and ARF was obtained by carrying out Poisson regression of the rate of ARF in terms of permethrin rate at the census area unit level, with adjustment for ethnicity and socio‐economic deprivation. Results: A total of 413 neighbourhoods were included. The incidence of ARF varied between 0 and 102 per 100 000 people per year (mean 4.3). In contrast, the annual incidence of dispensing of permethrin varied between 0 and 3201 per 100 000 people per year (mean 771). A strong association was observed between the two variables. In an adjusted quasi‐Poisson model, permethrin‐dispensing rates were strongly associated with ARF incidence, with a change from the 16th to the 84th centile associated with a 16.5‐fold increase in incidence (95% confidence interval: 3.82–71.6). Conclusions: Permethrin prescribing as an indicator of scabies is strongly associated with the incidence of ARF. Considered together with other studies, this evidence suggests that improving scabies control may reduce the burden of ARF in New Zealand.